Εντοπισμός , καταδίωξη και σύλληψη αλλοδαπών και του αλλοδαπού διακινητή τους στην Κω (HellenicCoastguard, 2022)
: Παρακαλώ! Παρακαλώ! Παρακαλώ! Παρακαλώ! Παρακαλώ! Παρακαλώ! Παρακαλώ! Παρακαλώ! Παρακαλώ! Παρακαλώ! Παρακαλώ! Παρακαλώ! Πήγε τα πόδια λάμπα! Πήγε τα πόδια! Πήγε τα πόδια! Πήγε τα πόδια! Πήγε τα πόδια! Πήγε τα πόδια! Πήγε τα πόδια!